A cement blanket and preparation method thereof
By introducing carbon nanotube reinforcement components and polyvinyl alcohol fibers into the cement matrix of the cement blanket and using silicone surfactant, the problem of poor mechanical properties of the cement blanket is solved, and the tensile strength, bending strength and impermeability resistance are significantly improved, expanding its application range in construction projects.
Patent Information
- Application Number
- CN202411084277.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-08-08
AI Technical Summary
The existing cement blankets have poor mechanical properties, especially the low tensile strength and bending strength, which limits their application range.
The mechanical properties of the cement blanket are improved by introducing carbon nanotube reinforcement components and polyvinyl alcohol fibers into the cement matrix and using silicone surfactants. The carbon nanotube reinforced components are made by combining carboxylated multi-walled carbon nanotubes with stearic acid. They have good thermal conductivity and low melting point characteristics. They can absorb heat generated by cement hydration and form a hydrophobic film, improving impermeability resistance.
It significantly improves the tensile strength and bending strength of cement blankets, enhances its impermeability, and gives it a wider application prospect in construction projects.
Smart Images

Figure BDA0004984715970000091 
Figure BDA0004984715970000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a cement blanket and a preparation method thereof. Background Art
[0002] Cement blanket, scientifically known as concrete canvas, is a three-dimensional spacer fabric reinforced cement composite material with a unique molding method and excellent performance. The molding characteristics of the three-dimensional fabric reinforced cement composite material are that the cement-based powder is pre-filled into the fiber fabric from the surface gap of the three-dimensional spacer fabric, and the cement is hydrated by sprinkling water, which hardens in a short time to form a thin concrete layer with both mechanical properties and durability. Compared with traditional concrete materials, it has the advantages of being easy to use and flexible in application. Therefore, cement blanket has a wide range of application prospects in the fields of rapid road repair, mountain slope protection, river bank reinforcement, ditch slope, underwater pipeline maintenance and other construction projects.
[0003] Since cement blanket adopts the preparation process of powder filling and the molding method of water sprinkling and hardening, the uniformity of cement powder in the three-dimensional spacer fabric and the particle packing density are poor, resulting in low tensile and bending strength after coagulation and hardening. The low tensile strength and bending strength will greatly limit the application of concrete canvas. Therefore, providing a cement blanket with good mechanical properties is a technical problem that needs to be solved at present. Summary of the invention
[0004] The purpose of the present invention is to provide a cement blanket and a preparation method thereof, so as to solve the problem that the existing cement blanket has poor mechanical properties.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A cement blanket comprises a cement matrix and a three-dimensional spacer fabric for filling the cement matrix. The cement matrix comprises sulphoaluminate cement clinker, semi-hydrated gypsum, a carbon nanotube reinforcing component, polyvinyl alcohol fiber, and an organosilicon surfactant. The mass ratio of the sulphoaluminate cement clinker, the semi-hydrated gypsum, the carbon nanotube reinforcing component, the polyvinyl alcohol fiber, and the organosilicon surfactant is 75-90:10-25:0.3-0.5:0.1-0.2:0.3-0.6.
[0007] The carbon nanotube reinforcement component is stearic acid filled carbon nanotubes.
[0008] Further, the carbon nanotube reinforced component is prepared by the following steps:
[0009] Place the carboxylated multi-walled carbon nanotubes in a flask, control the temperature at 80°C, use a vacuum pump to evacuate for 20-40 minutes, then inject the stearic acid benzene solution into the flask, keep the temperature for 20 minutes, filter, and dry the filter cake at 40°C to constant weight;
[0010] The mass ratio of carboxylated multi-walled carbon nanotubes to stearic acid is 1.2-1.5:0.8-1.2, and the mass ratio of stearic acid to benzene in the stearic acid benzene solution is 1:4.
[0011] Further, the organosilicon surfactant is prepared by the following steps:
[0012] Add 1,1,1,3,5,5,5-heptamethyltrisiloxane and chloroplatinic acid into a flask, raise the temperature to 80°C under nitrogen protection, add ethyl acrylate dropwise, raise the temperature to 100°C after the addition is complete, react for 4 hours, remove unreacted 1,1,1,3,5,5,5-heptamethyltrisiloxane and ethyl acrylate by rotary evaporation to obtain an intermediate product, add the intermediate product and anhydrous ethanol into a flask, add sodium hydroxide solution dropwise into the flask, react at 70°C for 3 hours, and finally remove anhydrous ethanol and water by rotary evaporation.
[0013] Furthermore, the dosage ratio of 1,1,1,3,5,5,5-heptamethyltrisiloxane, chloroplatinic acid, ethyl acrylate, anhydrous ethanol, and sodium hydroxide solution is 5.51 g: 0.333 g: 11.12 g: 70 mL: 7.5-8 mL, the sodium hydroxide solution is composed of sodium hydroxide and deionized water in a mass ratio of 1.88:7.52, and 1,1,1,3,5,5,5-heptamethyltrisiloxane and ethyl acrylate are used as raw materials to obtain an organosilicon surfactant through a hydrosilylation reaction and an ester hydrolysis reaction.
[0014] Furthermore, the sulphoaluminate cement clinker is sulphoaluminate cement clinker 72.5.
[0015] Furthermore, the semi-hydrated gypsum adopts α-type semi-hydrated gypsum.
[0016] Furthermore, the polyvinyl alcohol fiber has a length of 6-12 mm, a diameter of 15 μm, a breaking strength of ≥1200 MPa, an elastic modulus of ≥35 GPa, and a breaking elongation of 6-11%.
[0017] A method for preparing a cement blanket comprises the following steps:
[0018] (1) Sulphoaluminate cement clinker, hemihydrate gypsum, and organosilicon surfactant are passed through a 100-mesh sieve, placed in a mixer, and stirred for 15-25 minutes at a rotation speed of 135-145 r / min and a revolution speed of 57-67 r / min, then carbon nanotube reinforcement components and polyvinyl alcohol fibers are added, and stirring is continued for 10-20 minutes to obtain a cement matrix;
[0019] (2) placing the three-dimensional spacer fabric on a vibration platform, uniformly vibrating the cement matrix into the three-dimensional spacer fabric to obtain a solid-phase cement blanket, and then spraying water onto the solid-phase cement blanket to shape it and obtain a cement blanket.
[0020] Furthermore, the ratio of the mass of the cement matrix to the area of the three-dimensional spacer fabric is 130-150 g: 10 cm 2 .
[0021] Furthermore, the mass ratio of cement matrix to water is 1:0.45.
[0022] Furthermore, the spraying speed is 8-14 L / min.
[0023] Beneficial effects of the present invention:
[0024] The invention provides a cement blanket, which specifically uses sulphoaluminate cement clinker, semi-hydrated gypsum, silicone surfactant, carbon nanotube reinforcing component and polyvinyl alcohol fiber as raw materials, first prepares a cement matrix, and then fills it into a three-dimensional spacer fabric to obtain a cement blanket, which has the characteristics of short setting time, high tensile strength and bending strength, and high anti-seepage performance, is easy to construct and dismantle, and has good application prospects in the fields of construction projects such as rapid road repair, mountain slope protection, river bank reinforcement, ditch slope, underwater pipeline maintenance, etc.
[0025] The present invention introduces an organic silicon surfactant into the cement matrix. The organic silicon surfactant contains a sodium carboxylate hydrophilic group and a siloxane hydrophobic chain. During the curing process of the cement matrix, the organic silicon surfactant can react with the sodium carboxylate hydrophilic group and the siloxane hydrophobic chain. 2+ Ion complexation accelerates the dissolution rate of C3A in cement paste, thereby promoting the reaction of C3A with gypsum and accelerating the formation of ettringite crystals, showing a good accelerating effect. On the other hand, due to the presence of hydrophobic chains, it helps to improve the anti-permeability of cement blanket.
[0026] The present invention introduces carbon nanotube reinforcing components and polyvinyl alcohol fibers into a cement matrix. The carbon nanotube reinforcing components contain stearic acid. Based on the good thermal conductivity of the carbon nanotubes and the low melting point of the stearic acid, during the solidification process of the cement matrix, the carbon nanotube reinforcing components can absorb the heat generated by cement hydration, so that the stearic acid melts and flows out. The flowed stearic acid is adsorbed on the surface of cement particles, and the hydrophobic long chains are arranged on the outside to form a hydrophobic film, which makes it difficult for moisture to enter the interior of the cement blanket, and further improves the anti-seepage performance of the cement blanket. Since the polyvinyl alcohol fibers and carbon nanotubes have different elastic moduli and different scales, the mixture of the two can form a three-dimensional network in the cement blanket, improve the density of the cement blanket, reduce the germination of cracks, and inhibit the formation of cracks and penetrate cracks, thereby improving the mechanical properties of the cement blanket.
[0027] The invention fills stearic acid into the carboxylated multi-walled carbon nanotubes, and compared with directly adding a physical mixture of carboxylated multi-walled carbon nanotubes and stearic acid, the problem that stearic acid has strong air entraining capacity and has a great influence on the mechanical properties of concrete can be solved. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Carboxylated multi-walled carbon nanotubes were purchased from Suzhou Tanfeng Graphene Technology Co., Ltd., with the product brand HQNANO-CNTs-007-1C (outer diameter of 8-15 nm and length of 0.5-2 μm);
[0030] Sulphoaluminate cement clinker was sulphoaluminate cement clinker 72.5, purchased from Tangshan Polar Bear Building Materials Co., Ltd.;
[0031] The semi-hydrated gypsum used was α-type semi-hydrated gypsum, which was purchased from Hebei Mingzhe Mineral Products Co., Ltd.;
[0032] The polyvinyl alcohol fiber has a length of 6-12 mm, a diameter of 15 μm, a breaking strength of ≥1200 MPa, an elastic modulus of ≥35 GPa, and an elongation at break of 6-11%, and was purchased from Taian Haosong Fiber Co., Ltd.;
[0033] Three-dimensional spacer fabric: produced by Changshu Meishunqi Textile Technology Co., Ltd., polyester fiber warp knitting, spacer layer structure X-90°, thickness 18mm.
[0034] Example 1
[0035] This embodiment provides an organosilicon surfactant, which is prepared by the following steps:
[0036] Add 5.51g 1,1,1,3,5,5,5-heptamethyltrisiloxane and 0.333g chloroplatinic acid into a flask, raise the temperature to 80°C under nitrogen protection, add 11.12g ethyl acrylate dropwise, raise the temperature to 100°C after the addition is complete, react for 4h, remove unreacted 1,1,1,3,5,5,5-heptamethyltrisiloxane and ethyl acrylate by rotary evaporation to obtain an intermediate product, add the intermediate product and 70mL anhydrous ethanol into a flask, add 7.5mL sodium hydroxide solution into the flask, the sodium hydroxide solution is composed of sodium hydroxide and deionized water in a mass ratio of 1.88:7.52, react at 70°C for 3h, and finally remove anhydrous ethanol and water by rotary evaporation.
[0037] Example 2
[0038] This embodiment provides an organosilicon surfactant, which is prepared by the following steps:
[0039] Add 5.51g 1,1,1,3,5,5,5-heptamethyltrisiloxane and 0.333g chloroplatinic acid into a flask, raise the temperature to 80°C under nitrogen protection, add 11.12g ethyl acrylate dropwise, raise the temperature to 100°C after the addition is complete, react for 4h, remove unreacted 1,1,1,3,5,5,5-heptamethyltrisiloxane and ethyl acrylate by rotary evaporation to obtain an intermediate product, add the intermediate product and 70mL anhydrous ethanol into a flask, add 8mL sodium hydroxide solution into the flask, the sodium hydroxide solution is composed of sodium hydroxide and deionized water in a mass ratio of 1.88:7.52, react at 70°C for 3h, and finally remove anhydrous ethanol and water by rotary evaporation.
[0040] Example 3
[0041] A cement blanket comprises a cement matrix and a three-dimensional spacer fabric for filling the cement matrix, wherein the cement matrix comprises 75 g of sulphoaluminate cement clinker, 10 g of hemihydrate gypsum, 0.3 g of a carbon nanotube reinforcing component, 0.1 g of polyvinyl alcohol fiber, and 0.3 g of the organosilicon surfactant of Example 1.
[0042] The carbon nanotube reinforced component is prepared by the following steps:
[0043] 1.2 g of carboxylated multi-walled carbon nanotubes were placed in a flask, the temperature was controlled at 80°C, and after vacuuming with a vacuum pump for 20 minutes, a stearic acid benzene solution containing 0.8 g of stearic acid was injected into the flask, and the mass ratio of stearic acid to benzene in the stearic acid benzene solution was 1:4 (at the moment of injection, toluene evaporated and refluxed, and stearic acid immersed the acidified carbon nanotubes and entered the interior of the acidified carbon nanotubes), after keeping the temperature for 20 minutes, filtered, and the filter cake was dried at 40°C to constant weight;
[0044] The preparation method of the cement blanket comprises the following steps:
[0045] (1) Sulphoaluminate cement clinker, hemihydrate gypsum, and organosilicon surfactant were passed through a 100-mesh sieve, placed in a mixer, and stirred for 15 minutes at a rotation speed of 135 r / min and a revolution speed of 57 r / min, and then carbon nanotube reinforcement components and polyvinyl alcohol fibers were added, and stirring was continued for 10 minutes to obtain a cement matrix;
[0046] (2) The three-dimensional spacer fabric is placed on a vibration platform, and the cement matrix is evenly vibrated into the three-dimensional spacer fabric. The ratio of the mass of the cement matrix to the area of the three-dimensional spacer fabric is 130 g: 10 cm 2 , a solid cement blanket is obtained, and then water is sprayed onto the solid cement blanket, the mass ratio of cement matrix to water is 1:0.45, the spraying speed is 8L / min, and the blanket is formed to obtain a cement blanket.
[0047] Example 4
[0048] A cement blanket comprises a cement matrix and a three-dimensional spacer fabric for filling the cement matrix, wherein the cement matrix comprises 80 g of sulphoaluminate cement clinker, 18 g of hemihydrate gypsum, 0.4 g of a carbon nanotube reinforcing component, 0.1 g of polyvinyl alcohol fiber, and 0.45 g of the organosilicon surfactant of Example 2.
[0049] The carbon nanotube reinforced component is prepared by the following steps:
[0050] 1.4 g of carboxylated multi-walled carbon nanotubes were placed in a flask, the temperature was controlled at 80°C, and after vacuuming with a vacuum pump for 30 minutes, a stearic acid benzene solution containing 1.0 g of stearic acid was injected into the flask, and the mass ratio of stearic acid to benzene in the stearic acid benzene solution was 1:4 (at the moment of injection, toluene evaporated and refluxed, and stearic acid immersed the acidified carbon nanotubes and entered the interior of the acidified carbon nanotubes), after keeping the temperature for 20 minutes, filtered, and the filter cake was dried at 40°C to constant weight;
[0051] The preparation method of the cement blanket comprises the following steps:
[0052] (1) Sulphoaluminate cement clinker, hemihydrate gypsum, and organosilicon surfactant were passed through a 100-mesh sieve, placed in a mixer, and stirred at a rotation speed of 140 r / min and a revolution speed of 60 r / min for 20 min, then carbon nanotube reinforcement components and polyvinyl alcohol fibers were added, and stirring was continued for 15 min to obtain a cement matrix;
[0053] (2) The three-dimensional spacer fabric is placed on a vibration platform, and the cement matrix is evenly vibrated into the three-dimensional spacer fabric. The ratio of the mass of the cement matrix to the area of the three-dimensional spacer fabric is 140 g: 10 cm 2 , a solid cement blanket is obtained, and then water is sprayed onto the solid cement blanket, the mass ratio of cement matrix to water is 1:0.45, the spraying speed is 10L / min, and the blanket is formed to obtain a cement blanket.
[0054] Example 5
[0055] A cement blanket comprises a cement matrix and a three-dimensional spacer fabric for filling the cement matrix, wherein the cement matrix comprises 90 g of sulphoaluminate cement clinker, 25 g of hemihydrate gypsum, 0.5 g of a carbon nanotube reinforcing component, 0.2 g of polyvinyl alcohol fiber, and 0.6 g of the organosilicon surfactant of Example 2.
[0056] The carbon nanotube reinforced component is prepared by the following steps:
[0057] 1.5 g of carboxylated multi-walled carbon nanotubes were placed in a flask, the temperature was controlled at 80°C, and after vacuuming with a vacuum pump for 40 minutes, a stearic acid benzene solution containing 1.2 g of stearic acid was injected into the flask, and the mass ratio of stearic acid to benzene in the stearic acid benzene solution was 1:4 (at the moment of injection, toluene evaporated and refluxed, and stearic acid immersed the acidified carbon nanotubes and entered the interior of the acidified carbon nanotubes), after keeping the temperature for 20 minutes, filtered, and the filter cake was dried at 40°C to constant weight;
[0058] The preparation method of the cement blanket comprises the following steps:
[0059] (1) Sulphoaluminate cement clinker, hemihydrate gypsum, and organosilicon surfactant were passed through a 100-mesh sieve, placed in a mixer, and stirred at a rotation speed of 145 r / min and a revolution speed of 67 r / min for 25 min, then carbon nanotube reinforcement components and polyvinyl alcohol fibers were added, and stirring was continued for 20 min to obtain a cement matrix;
[0060] (2) The three-dimensional spacer fabric is placed on a vibration platform, and the cement matrix is evenly vibrated into the three-dimensional spacer fabric. The ratio of the mass of the cement matrix to the area of the three-dimensional spacer fabric is 150 g: 10 cm 2 , a solid cement blanket is obtained, and then water is sprayed onto the solid cement blanket, the mass ratio of cement matrix to water is 1:0.45, the spraying speed is 14L / min, and the blanket is formed to obtain a cement blanket.
[0061] Comparative Example 1
[0062] A cement blanket, compared with Example 3, the organosilicon surfactant in the cement matrix of Example 3 is removed, and the remaining raw materials and preparation process are the same as Example 3.
[0063] Comparative Example 2
[0064] A cement blanket, compared with Example 3, the carbon nanotube reinforcing component in the cement matrix of Example 3 is replaced by "a mixture obtained by stirring carboxylated multi-walled carbon nanotubes and stearic acid in a mass ratio of 1.2:0.8 in a stirrer at 200 rpm for 20 minutes", and the remaining raw materials and preparation process are the same as Example 3.
[0065] Comparative Example 3
[0066] A cement blanket, compared with Example 3, the carbon nanotube reinforcement component in the cement matrix of Example 3 is replaced with carboxylated multi-walled carbon nanotubes, and the remaining raw materials and preparation process are the same as Example 3.
[0067] Comparative Example 4
[0068] A cement blanket, compared with Example 3, the carbon nanotube reinforcement component in the cement matrix of Example 3 is removed, and the remaining raw materials and preparation process are the same as Example 3.
[0069] According to the standard "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency" (GB / T1346-2011), the setting time of the cement matrix obtained in Examples 3-5 and Comparative Examples 1-4 was tested, and the water-cement ratio was determined to be 0.45;
[0070] Referring to the Test Method for Strength of Cement Mortar (GB / T17671-1999) ISO, a 40 mm × 40 mm × 160 mm triple test block was prepared using the cement matrix obtained in Examples 3-5 and Comparative Examples 1-4. The formed test pieces were placed in a standard curing box with a relative humidity of not less than 90% and a temperature of (20 ± 1) ° C, and the compressive and flexural strength values at the corresponding age were measured;
[0071] The concrete impermeability test method in BS-EN12390-8:2009 "Depth of water penetration under pressure" was adopted, with a 150mm×150mm×150mm test block, an age of 28 days, and a water pressure of (500±25) kPa, which was maintained for 24 hours. During the test, attention should be paid to observing whether there is water leaching on the non-water pressure surface of the sample. If leakage occurs, the accuracy of the test should be re-evaluated. During the test, the maximum water seepage height of the concrete under water pressure for 24 hours was recorded respectively.
[0072] The results of the setting time test are shown in Table 1:
[0073] Table 1
[0074]
[0075] It can be seen from the test results in Table 1 that, compared with the cement matrix used in the cement blanket prepared in Comparative Examples 1-4, the cement matrix used in the cement blanket prepared in Examples 3-5 has the advantages of short setting time, high compressive and flexural strength, and high anti-permeability performance;
[0076] The tensile properties of cement blankets obtained in Examples 3 to 5 and Comparative Examples 1 to 4 were tested with reference to GB / T1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics". The results are shown in Table 2:
[0077] Table 2
[0078]
[0079] It can be seen from the test results in Table 2 that compared with the cement blankets prepared in Comparative Examples 1-4, the cement blankets prepared in Examples 3-5 have better mechanical properties.
[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A cement blanket, comprising a cement matrix and a three-dimensional spacer fabric for filling the cement matrix, characterized in that: The cement matrix includes sulphoaluminate cement clinker, hemihydrate gypsum, carbon nanotube reinforcing component, polyvinyl alcohol fiber, and silicone surfactant, and the mass ratio of sulphoaluminate cement clinker, hemihydrate gypsum, carbon nanotube reinforcing component, polyvinyl alcohol fiber, and silicone surfactant is 75-90:10-25:0.3-0.5:0.1-0.2:0.3-0.6; The carbon nanotube reinforcement component is stearic acid filled carbon nanotubes.
2. A cement blanket according to claim 1, characterized in that: The carbon nanotube reinforced component is prepared by the following steps: Place the carboxylated multi-walled carbon nanotubes in a flask, control the temperature at 80°C, use a vacuum pump to evacuate for 20-40 minutes, then inject the stearic acid benzene solution into the flask, keep the temperature for 20 minutes, filter, and dry the filter cake at 40°C to constant weight.
3. A cement blanket according to claim 2, characterized in that: The mass ratio of carboxylated multi-walled carbon nanotubes to stearic acid is 1.2-1.5:0.8-1.2, and the mass ratio of stearic acid to benzene in the stearic acid benzene solution is 1:
4.
4. A cement blanket according to claim 1, characterized in that: Silicone surfactants are made by the following steps: Add 1,1,1,3,5,5,5-heptamethyltrisiloxane and chloroplatinic acid to a flask, raise the temperature to 80°C under nitrogen protection, add ethyl acrylate dropwise, raise the temperature to 100°C after the addition is complete, react for 4 hours, remove unreacted 1,1,1,3,5,5,5-heptamethyltrisiloxane and ethyl acrylate by rotary evaporation to obtain an intermediate product, add the intermediate product and anhydrous ethanol to a flask, add sodium hydroxide solution dropwise to the flask, react at 70°C for 3 hours, and finally remove anhydrous ethanol and water by rotary evaporation.
5. A cement blanket according to claim 4, characterized in that: The dosage ratio of 1,1,1,3,5,5,5-heptamethyltrisiloxane, chloroplatinic acid, ethyl acrylate, anhydrous ethanol and sodium hydroxide solution is 5.51 g: 0.333 g: 11.12 g: 70 mL: 7.5-8 mL, and the sodium hydroxide solution is composed of sodium hydroxide and deionized water in a mass ratio of 1.88:7.
52.
6. A cement blanket according to claim 1, characterized in that: The semi-hydrated gypsum adopts α-type semi-hydrated gypsum.
7. A cement blanket according to claim 1, characterized in that: The polyvinyl alcohol fiber has a length of 6-12 mm, a diameter of 15 μm, a breaking strength of ≥1200 MPa, an elastic modulus of ≥35 GPa, and a breaking elongation of 6-11%.
8. A method for preparing a cement blanket according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Sulphoaluminate cement clinker, hemihydrate gypsum, and organosilicon surfactant are passed through a 100-mesh sieve, placed in a mixer, and stirred for 15-25 minutes, then carbon nanotube reinforcement components and polyvinyl alcohol fibers are added, and stirring is continued for 10-20 minutes to obtain a cement matrix; (2) placing the three-dimensional spacer fabric on a vibration platform, uniformly vibrating the cement matrix into the three-dimensional spacer fabric to obtain a solid-phase cement blanket, and then spraying water onto the solid-phase cement blanket to shape it and obtain a cement blanket.
9. The method for preparing a cement blanket according to claim 8, characterized in that: The ratio of the mass of the cement matrix to the area of the three-dimensional spacer fabric is 130-150 g:10 cm 2 .
10. The method for preparing a cement blanket according to claim 8, characterized in that: The mass ratio of cement matrix to water is 1:0.45.
Citation Information
Patent Citations
Protective slurry for surface of concrete canvas outdoor furniture and treatment method
CN117165104A
Cement-based electromagnetic wave-absorbing canvas tent
CN117947992A
Cited By
Non-woven quilting cement-based composite material blanket with impermeable backing bottom film
CN224063526U